Photogrammetry—The Science of Precise Measurements from Images: A Themed Issue in Honour of Professor Emeritus Armin Grün in Anticipation of His 80th Birthday - Rongjun Qin; Devrim Akca; Fabio Remondino (Remote Sensing)
Photogrammetry has been a cornerstone in mapping history and still functions as one of the key techniques in modern geospatial science and engineering [...]